Movement of Sediment Through a Burned Landscape: Sediment Volume Observations and Model Comparisons in the San Gabriel Mountains, California, USA. Issue 7 (9th July 2021) - Rengers, F. K.; McGuire, Luke A.; Kean, Jason W.; Staley, Dennis M.; Dobre, Mariana; Robichaud, Peter R.; Swetnam, Tyson
Abstract: Post‐wildfire changes to hydrologic and geomorphic systems can lead to widespread sediment redistribution. Understanding how sediment moves through a watershed is crucial for assessing hazards, developing debris flow inundation models, engineering sediment retention solutions, and quantifying the role that disturbances play in landscape evolution. In this study, we used terrestrial and airborne lidar to measure sediment redistribution in the 2016 Fish Fire, in the San Gabriel Mountains in southern California, USA. The lidar areas are in two adjacent watersheds, at spatial scales of 900 m 2 to 4 km 2, respectively. Terrestrial lidar data were acquired prior to rainfall, and two subsequent surveys show erosional change after rainstorms. Two airborne lidar flights occurred (1) 7 months before, and (2) 14 months after the fire ignition, capturing the erosional effects after rainfall. We found hillslope erosion dominated the overall sediment budget in the first rainy season after wildfire. Only 7% of the total erosion came from the active channel bed and channel banks, and the remaining 93% of eroded sediment was derived from hillslopes. Within the channelized portion of the watershed erosion/deposition could be generally described with topographic metrics used in a stream power equation. Observed sediment volumes were compared with four empirical models and one process‐based model. We found that the best predictions of sediment volume were obtained from an empirical model developed in the same physiographic region. Moreover, this study showed that post‐wildfire erosion rates in the San Gabriel Mountains attain the same magnitude as millennial time scale bedrock erosion rates. Plain Language Summary: Debris flows are mixtures of water and sediment that move swiftly downhill, damaging property and threatening lives. Rainfall on steep mountainous slopes burned by wildfire can generate these debris flows, creating a substantial risk. It is difficult to create evacuation plans or to build appropriate mitigation structures to capture debris flow sediment downstream of steep, burned slopes if we don'|'t know how to estimate the volume of sediment that might flow downhill. This study uses observations of erosion and deposition in a burned watershed to calculate the volume of sediment moved, and to map where the sediment was removed and deposited. We compared the observations with known models to test the model predictions. We found that most of the sediment was moved from hillslope areas, and then redeposited downstream in low‐lying areas of the channel, primarily downstream of the mountain front. Key Points: The majority of sediment eroded after a wildfire in the San Gabriel Mountains originated from hillslopes Post‐fire sediment volumes were best predicted by an empirical model developed in the same physiographic region Year one post‐wildfire erosion rates are similar in magnitude to the long‐term bedrock erosion rates in the San Gabriel Mountains